Strength Properties of Polymer Reactive Powder Concrete with Waste Materials - Shatha Sadiq Hasan; Mohammed Y. Fattah (Civil Engineering Journal, 2023)
Reactive powder concrete, or RPC, outperforms conventional or even high-performance concrete in terms of ultra-high strength and better durability. Several buildings were destroyed in Iraq, and recycling the garbage from these buildings can significantly help reduce waste and environmental pollution as well as serve as a source of aggregate for use in new construction. Reusing garbage and using sustainable building materials are now crucial environmental challenges, so this study aimed to replace the natural fine aggregate, NFA, used in preparations of polymer reactive powder concreter, "PRPC" with recycled aggregates, or RA, from crushed old concrete, COC, in order to make PRPC production more environmentally and sustainably friendly. In this study, RPC is modified by adding styrene butadiene rubber (SBR), a polymer, to the original mixture at a ratio of 13% by weight of cement. This study sought to determine the effect of using COC as recycled fine aggregate (RFA) on the compressive, splitting, and flexural strengths of PRPC. The main objective of this investigation is to study the effect of oil (water, new oil, and waste engine oil) on the compressive and tensile strengths of PRPC with COC and to compare the behavior with that of a control mix (PRPC with NFA). The mixtures were prepared using six different percentages of RFA, replacing 0, 20, 40, 60, 80, and 100% NfA. After 28 days, the six mixes were divided into three groups. The first was still being cured in water, W; the second in waste engine oil, WEO; and the third in kerosene oil, KO. The results showed that using COC as RFA in PRPC was viable, and according to this investigation, the mix with 40% COC replacement with NFA provides the highest values of compressive strength, tensile strength, and flexural strength before and after exposure to liquids (water, new oil, and waste engine oil).Â Doi: 10.28991/CEJ-2023-09-08-09 Full Text: PDF